Peran Komite Sekolah dalam Meningkatkan Kualitas Pelayanan - Edi Susanto; Ahmad Tohardi; Ari Juliana (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to describe the role of the school committee in improving the quality of services at SMA Negeri 1 Sepauk, Sintang Regency. This research uses a case study type of research. This research was carried out at SMA Negeri 1 Sepauk, Sintang Regency. Data collection techniques include observation, interviews, and documentation using the data analysis technique Analysis Interactive Model from Miles and Huberman. The results of the research show that the role of the committee is to provide consideration for its implementation in the form of giving input on the education management process in schools. The role of the school committee as a supporting body for the implementation and efforts to improve the quality of services, especially Islamic religious education, can take the form of financial support, energy, and mental support. The role of the committee as a mediator so far takes the form of relationships between the principal and the community, the principal and the education board, and the principal and the school itself. In conclusion, the role of the school committee in improving the quality of service at SMA Negeri 1 Sepauk Sintang Regency can act as a consideration provider, a supporter, and as a mediator. Keywords: Improving Service Quality, Role of School Committees.